Cultural Situation after the War of Independence and the Poetry of Akbar Allahabadi - Hassan, Uzma (sourcecoder, 2023)
The British who entered the Indian subcontinent for the purpose of trade and over time being opportunistic eventually took the crown and ruled for more than ninety years. During this period, he also introduced his own education system to train his subjugated nation. The main aim of this system of education was to produce a batch of students who are Indian in terms of color, race and lips and accent, but British in moral and intellectual terms. The British, by using a lot of propaganda, gave the impression that they alone were responsible for the development and prosperity of India. However, the reality was quite the opposite. India's loot was the cause of England's prosperity. Akbar Allahabadi seems to criticize the propagation and imitation of Western civilization. Where Western civilization was alienating the local people from religion, there was a strong effort to subjugate science and philosophy in comparison to religion. The modern educated class had established the awe of the West on their minds to such an extent that the West was in every field of life. Akbar Allahabadi fulfilled the duty of leading the nation by bringing this situation under observation.